Visual search strategies in a shared zone in pedestrians with and without intellectual disability. (November 2019) - Earl, Robyn; Morris, Susan; Girdler, Sonya; Falkmer, Torbjorn; Cowan, Georgia; Falkmer, Marita
Highlights: Participants with ID were less likely to look at traffic relevant objects compared with the control group. All participants attended more to traffic relevant objects at the zebra crossing compared with the shared zone. Males with ID were almost four times less likely to look at traffic relevant objects compared with females with ID. Abstract: People with intellectual disability (ID) may find shared zones troublesome to negotiate because of the lack of the traditional clearly defined rules and boundaries. With the built environment identified as a barrier to active travel and community access, it is vital to explore how pedestrians with ID navigate shared zones to ensure that this group is not placed in harm's way or discouraged from active travel because of the implications of shared zones. This study investigated the visual strategies of 19 adults with ID and 21 controls who wore head mounted eye trackers in a Shared Zone and at a zebra crossing (as a contrast traffic environment). In total 4750 valid fixations were analysed. Participants with ID fixated on traffic relevant objects at a rate of 68 percent of the control participants. Furthermore, the males with ID were 9(4.4–18.7) times more likely to fixate on non-traffic relevant objects compared with traffic relevant objects, much higher odds than that of females with ID 1.8(0.4–1.7). Zebra crossings appeared to act as a cue, drawing pedestrians' visual attention to the traffic environment, with both groups more likely to look at traffic relevant objects on/at the zebra crossing (66%: 34%). Future implementation of shared zones needs to be carefully considered in relation to the safety of road users with ID and their capacity to identify and assess salient environmental information.